Rancang Bangun Sistem Informasi Pembayaran Biaya Pendidikan Pada Politeknik Lp3i Jakarta Kampus Bekasi - Dyan Yuliana; Fadly Putra Arafah (Lembaga Pengembangan Kinerja Dosen, 2022)
The process of paying tuition fees applied at the LP3I Jakarta Polytechnic, Bekasi Campus,currently still uses conventional methods, namely by recording on receipts and assisted byMicrosoft Office Excel, so that the process of paying tuition fees runs less effectively andefficiently. From these problems, the idea emerged to create a web-based information system,which was able to manage the payment of education costs in a computerized manner. Theresearch methods used are Library Research and Field Research, the application software usedis SublimeText, XAMPP, MySQL with PHP version 7. There is one actor in this informationsystem, namely the cashier. Cashiers can access and manage cashier data, installment data,student data, transaction data and report data. With the existence of the Education Fee PaymentInformation System at the LP3I Polytechnic Jakarta Bekasi Campus, it is hoped that it canfacilitate the process of paying tuition fees.